Food packaging and shelf life : a practical guide - Robertson, Gordon L. , 1946- (Boca Raton, FL : CRC Press/Taylor & Francis, 2010)
"The importance of packaging hardly needs stressing since only a handful of foods are sold in an unpackaged state. With an increasing focus on sustainability and cost-effectiveness, responsible companies no longer want to over-package their food products, yet many remain unsure just where reductions can effectively be made. Food Packaging and Shelf Life: A Practical Guide provides package developers with the information they need to specify just the right amount of protective packaging to maintain food quality and maximize shelf life. Current food packaging must take into consideration the biochemical, chemical, physical, and biological changes that occur during processing, distribution, and storage. Organized according to chapters devoted to specific food products, this practical handbook defines - for the first time - the indices of failure for foods as diverse as milk, fruits, bottled water, juices, vegetables, fish, and beef. It discusses the deteriorative reactions for each and reviews how different packaging materials may influence time to failure and thus shelf life."--Publisher's description.
1. Food packaging and shelf life -- 2. Food quality and indices of failure -- 3. Shelf life testing methodology and data analysis -- 4. Packaging and the microbial shelf life of food -- 5. Packaging and the shelf life of milk -- 6. Packaging and the shelf life of cheese -- 7. Packaging and the shelf life of milk powders -- 8. Packaging and the shelf life of yogurt -- 9. Packaging and the shelf life of water and carbonated drinks -- 10. Packaging and the shelf life of orange juice -- 11. Packaging and the shelf life of coffee -- 12. Packaging and the shelf life of beer -- 13. Packaging and the shelf life of wine -- 14. Packaging and the shelf life of fresh red and poultry meats -- 15. Packaging and the shelf life of fish -- 16. Packaging and the shelf life of fruits and vegetables -- 17. Packaging and the shelf life of vegetable oils -- 18. Packaging and the shelf life of cereals and snack foods -- 19. Shelf life of foods in biobased packaging -- 20. Active packaging and the shelf life of foods
Includes bibliographical references and index
Keywords: Food -- Packaging